Cyber Security and Privacy 4th Cyber Security and Privacy Innovation Forum, CSP Innovation Forum 2015, Brussels, Belgium April 28-29, 2015, Revised Selected Papers - Cleary, Frances.; Cleary, Frances.; Felici, Massimo.; Felici, Massimo. (Communications in Computer and Information Science, 2015)
This book constitutes the thoroughly refereed selected papers on the 4th Cyber Security and Privacy Innovation Forum, CSP Forum 2015, held in Brussels, Belgium, in April 2015. The 12 revised full papers presented were carefully reviewed and selected from various submissions. The papers are organized in topical sections such as security and privacy in the cloud; security and privacy technologies; risk and trust; research and innovation in cyber security and privacy.